1993
DOI: 10.1007/bf00196441
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of three new occlusive dressings for healing of graft donor sites versus conventional therapy

Abstract: A comparative study of four skin graft donor site dressings was undertaken. This was a prospective and cross-over study of 25 consecutive patients with burns up to 40% TBSA treated with split skin grafts. Each donor site was divided into four sections and covered with different dressings in order to evaluate their effectiveness in healing, the time required for complete epithelialization, patient acceptance and any intolerance or local infection. The results showed that the occlusive hydrocolloid dressing sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…The other study did show a statistically significant difference although the comparison was made between a standard thickness product and a thin style, which would not be expected to perform to the same level 14 . The one study comparing different hydrocolloids with regard to infection showed no significant difference 15 …”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…The other study did show a statistically significant difference although the comparison was made between a standard thickness product and a thin style, which would not be expected to perform to the same level 14 . The one study comparing different hydrocolloids with regard to infection showed no significant difference 15 …”
Section: Resultsmentioning
confidence: 90%
“…There were a very limited number of studies of sufficient quality that made comparisons between different hydrocolloid dressings. In relation to the outcome of days to complete healing one study showed no significant difference between different hydrocolloids 15 . The other study did show a statistically significant difference although the comparison was made between a standard thickness product and a thin style, which would not be expected to perform to the same level 14 .…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations